Exploring effects of brief daily exposure to unfamiliar accent on listening performance and cognitive load - McLaughlin, Drew J.; Baese-Berk, Melissa M.; Van Engen, Kristin J. (Frontiers in Language Sciences, 2024)
Listeners rapidly "tune" to unfamiliar accented speech, and some evidence also suggests that they may improve over multiple days of exposure. The present study aimed to measure accommodation of unfamiliar second language-(L2-) accented speech over a consecutive fiveday period using both a measure of listening performance (speech recognition accuracy) and a measure of cognitive load (a dual-task paradigm). All subjects completed a dual-task paradigm with L1 and L2 accent on Days 1 and 5, and were given brief exposure to either L1 (control group) or unfamiliar L2 (training groups) accent on Days 2-4. One training group was exposed to the L2 accent via a standard speech transcription task while the other was exposed to the L2 accent via a transcription task that included implicit feedback (i.e., showing the correct answer after each trial). Although overall improvement in listening performance and reduction in cognitive load were observed from Day 1 to Day 5, our results indicated neither a larger benefit for the L2 accent training groups compared to the control group nor a difference based on the implicit feedback manipulation. We conclude that the L2 accent trainings implemented in the present study did not successfully promote long-term learning benefits of a statistically meaningful magnitude, presenting the findings of the present study as a methodologically informative starting point for future research on this topic.